PENGELOLAAN PEMBELAJARAN BERBASIS SISWA DI SMP QORYAH THOYYIBAH KALIBENING SALATIGA - YASIN , M. ZUBAIR ALI (2011)
The objectives of this research are (1) to describe the characteristics of materials of learning management based students at the Junior High School Qaryah Thayyibah Kalibening Salatiga, (2) Describe the characteristics of interaction of learning management based students at the Junior High School Qaryah Thayyibah Kalibening Salatiga. This is qualitative research and conducted in the Junior High School Qaryah Thayyibah Kalibening Salatiga. The main subjects in this research are managers, teachers and students in Junior High School Qoryah Toyyibah Kalibening, Salatiga. Data collection techniques in this research used observation, interview and documentation. The data analysis technique in this research used the analysis model of data collection, data reduction, data presentation, and conclusion. The validity of the data in this research includes credibility, transferability (external validity), dependability (reliability), and conformability (objectivity). The results of this research (1) the management of learning material in Junior High School Qoryah Toyyibah is done according to students' will. The student is free to choose the learning material and learning method that student's want. The student is made a group consist of 9 until 12 students to discuss learning material that they want. In giving the learning material, the student is guided by facilitator. (2) Learning interaction based students in Junior High School Qaryah Thayyibah been running in both directions. The school was never restricting students to conduct activities in accordance with the interests and agreements respectively. Teacher assistants also never require students to master the entire subject matter that learned in class. The atmosphere of learning is built without any fear and anger accompanying regulations or overwhelmed by school work.